2013
DOI: 10.1016/j.phrp.2013.10.007
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Antibacterial Efficacy of 21 Indian Timber-Yielding Plants Against Multidrug-Resistant Bacteria Causing Urinary Tract Infection

Abstract: ObjectivesTo screen methanolic leaf extracts of 21 timber-yielding plants for antibacterial activity against nine species of uropathogenic bacteria isolated from clinical samples of a hospital (Enterococcus faecalis, Staphylococcus aureus, Acinetobacter baumannii, Citrobacter freundii, Enterobacter aerogenes, Escherichia coli, Klebsiella pneumoniae, Proteus mirabilis, and Pseudomonas aeruginosa).MethodsBacterial strains were subjected to antibiotic sensitivity tests by the Kirby–Bauer's disc diffusion method. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 33 publications
1
27
0
1
Order By: Relevance
“…Polar extracts (methanol and water) of bark of S. oleosa showed strong bacterial inhibition (Figure 1 and Table 1) to both Gram-positive and Gram-negative bacteria. Similar fractions from the leaves of S. oleosa were reported to inhibit few bacterial strains [13,26]. Both the extracts effectively inhibited S. marcescens, E. coli, M. luteus and B. subtilis while the inhibition was not clearly transparent for S. aureus.…”
Section: Resultsmentioning
confidence: 57%
“…Polar extracts (methanol and water) of bark of S. oleosa showed strong bacterial inhibition (Figure 1 and Table 1) to both Gram-positive and Gram-negative bacteria. Similar fractions from the leaves of S. oleosa were reported to inhibit few bacterial strains [13,26]. Both the extracts effectively inhibited S. marcescens, E. coli, M. luteus and B. subtilis while the inhibition was not clearly transparent for S. aureus.…”
Section: Resultsmentioning
confidence: 57%
“…[34] Tannins as a Phytoconstituents, inhibit several extracellular bacterial enzymes, affect microbial metabolism by inhibiting oxidative phosphorylation and minimize the availability of essential metal ions by formation of metal complexes. [35] Flavonoids and alkaloids are also important plant constituents for exerting antifungal and antibacterial activity.…”
Section: Antibacterial and Anti-mycotic Effectmentioning
confidence: 99%
“…It was concluded that the leaves extract is a promising source for anticandidal compounds. Sometimes compounds present in plant extract are responsible for their partition into the lipid bilayer of the cell membrane, leading to an alteration of permeability and a consequent leakage of cell contents 3,4,8,25 . CONCLUSION: This research work has shown that the DMSO leaves extract of CF has potent antifungal action and this action was much more pronounced with fluconazole.…”
Section: Synergistic Effect Of Cf Leaves Extract and Fluconazole On Imentioning
confidence: 99%
“…On this study, we assess the synergism between Flu with CF (Cassia fistula). CF is called as 'An Indian Laburnum', also known as the golden shower tree and is a flowering plant belongs to the family Fabaceae 8 . The species is native to the Indian Subcontinent and adjacent regions of Southeast Asia and has antifungal properties 9 , hepato protective activity 10 , hypo cholesteroleamic activity 11 , hypo glucamic activity 12 , anti plasmodial activity 13 and anti-tumour activity 14 .…”
Section: Introductionmentioning
confidence: 99%